FOREIGN INSTITUTIONAL OWNERSHIP AND CASH HOLDINGS IN INDONESIA CAPITAL MARKET - Chandra, Ramadhani; Rahman, Annisaa (Jurnal Akuntansi Kontemporer, 2023)
Research Purpose. The purpose of research is analyzing the effect of foreign institutional ownership on cash holding, based on precautionary motive.Research Method. This research uses quantitative methods, with single independent variables (foreign institutional ownership). Cash holding (dependent variable) measured using the formula logaritma cash and cash equivalents. Population used in the study is all non-financial companies listed on the Indonesia Stock Exchange 2017-2019. The purposive sampling method used and obtained 1170 firm-year samples. Secondary data sourced from annual reports and financial statement and data analyzed using multiple linear regression analysis with variabel control (leverage).Research Result and Findings. The results of this study indicate that the foreign institutional ownership has positive effect on cash holding.